Immature Dendritic Cell-Derived Exosomes Rescue Septic Animals Via Milk Fat Globule Epidermal Growth Factor VIII - Michael Miksa; Rongqian Wu; Weifeng Dong; Hidefumi Komura; Dhruv Amin; Youxin Ji; Zhimin Wang; Haichao Wang; Thanjavur S. Ravikumar; Kevin J. Tracey; Ping Wang (2009)
Sepsis, a highly lethal systemic inflammatory syndrome, is associated with increases of proinflammatory cytokines (e.g., TNF-alpha, HMGB1) and the accumulation of apoptotic cells that have the potential to be detrimental. Depending on the timing and tissue, prevention of apoptosis in sepsis is beneficial; however, thwarting the development of secondary necrosis through the active removal of apoptotic cells by phagocytosis may offer a novel anti-sepsis therapy. Immature dendritic cells (IDCs) release exosomes that contain milk fat globule EGF factor VIII (MFGE8), a protein required to opsonize apoptotic cells for phagocytosis. In an experimental sepsis model using cecal ligation and puncture, we found that MFGE8 levels decreased in the spleen and blood, which was associated with impaired apoptotic cell clearance. Administration of IDC-derived exosomes promoted phagocytosis of apoptotic cells and significantly reduced mortality. Treatment with recombinant MFGE8 was equally protective, whereas MFGE8-deficient mice suffered from increased mortality. IDC exosomes also attenuated the release of proinflammatory cytokines in septic rats. Liberation of HMGB1, a nuclear protein that contributes to inflammation upon release from unengulfed apoptotic cells, was prevented by MFGE8-mediated phagocytosis in vitro. We conclude that IDC-derived exosomes attenuate the acute systemic inflammatory response in sepsis by enhancing apoptotic cell clearance via MFGE8.